KONTRIBUSI PRODUK SEKUNDER AMPAS TAHU PADA USAHA INDUSTRI RUMAH TANGGA UD. DUA PUTRI DI DESA GUNUNG ANTASARI KECAMATAN SIMPANG EMPAT KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Fitri Mahyudi; Husinsyah Husinsyah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
This Research aim to know technically about Seconder Product Contribution of Tofu Dregs UD Dua Putri Home Industries in Gunung Sari Village Simpang Empat Subdistrict Tanah Bumbu Regency City South Kalimantan Province. From result of knowable analysis that level of amount of acceptance from result of processing know Rp. 5.040.000/day and Rp. 151.200.000/month. Others at this tofu home industry there are addition of acceptance from tofu dregs know yield up with detail in 1 day yield 230 kg /day  and 6.900 kg dregs each month. Price sell tofu dregs know per kg Rp.1.000,-, hence result of total acceptance from tofu dregs know equal to Rp. 230.000/day and Rp.6.900.000/month. Become total acceptance from effort UD. Two Putri tofu home industry equal to Rp.5.270.000,-/Hari and Rp. 158.100.000,-/month. From result analyse known benefit effort processing know equal to Rp. 61.508.652,79,/month.